2021
DOI: 10.1055/a-1337-2961
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Age on Match-related Acceleration and Deceleration Efforts in Elite Soccer Players

Abstract: The aim of this study was to examine the effects of chronological age on acceleration and deceleration match performance in professional soccer players. A total of 5317 individual match observations were collected on 420 professional players competing in the Spanish LaLiga during the 2018–2019 season, using a multiple-camera computerised tracking system (TRACAB; ChyronHego, Melville, NY, USA). Players were classified using a k-means cluster analysis into four different age groups: 17–23 years, 24–27 years, 28–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…As a result of a growing scientific interest, several recent studies have investigated the relationship between age and match performance in elite soccer players. [5][6][7][8][9] Using cross-sectional approaches, these previous studies generally showed age-related decreases of match-running performance in professional-elite older players (>30 years), increasing the body of evidence in this field. However, to the best of our knowledge, there is no studies that have analyzed the effects of ageing on match-related performance of elite soccer players using a longitudinal design.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of a growing scientific interest, several recent studies have investigated the relationship between age and match performance in elite soccer players. [5][6][7][8][9] Using cross-sectional approaches, these previous studies generally showed age-related decreases of match-running performance in professional-elite older players (>30 years), increasing the body of evidence in this field. However, to the best of our knowledge, there is no studies that have analyzed the effects of ageing on match-related performance of elite soccer players using a longitudinal design.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…2,4 Additionally, recent studies examining match physical performance showed that players over 30 years perform significantly lower in the total distance covered, high-intensity activities, sprint distance and the number of accelerations and decelerations. [5][6][7][8][9] These age-related physical performance declines are more pronounced among central defenders, central midfielders and forwards. However, very few studies have studied the changes in technical-tactical performance of elite players according to their chronological age.…”
Section: Introductionmentioning
confidence: 99%
“…Previous authors have shown an overall decrease in physical match-performance in older elite soccer players, especially those 30 years of age and more. 2931…”
Section: Discussionmentioning
confidence: 99%
“…Previous authors have shown an overall decrease in physical match-performance in older elite soccer players, especially those 30 years of age and more. [29][30][31] Indeed, consistent with the above notion, a significant percentage (40%) of the players included within the present sample had turned 30 years before the start of the 2019-2020 season. A decrease in match running variables could also be explained by an improved organisation of the team tactically, as the coaching staff in the examined RPL team in the present study remained consistent over the five consecutive seasons.…”
Section: Between-season Analysismentioning
confidence: 99%
“…In sports analytics, there seems to be a limited literature on the relationship between maximum acceleration involving soccer specific movements and age. Lorenzo-Martinez et al 1 classified 420 La Liga players into four age groups, and found that older players (31–38 years of age) had fewer accelerations and decelerations per match than players 17–23 years, 24–27 years and 28–30 years. However, their findings revealed no significant age-related declines in players’ maximum acceleration, and only trivial differences were observed in maximum deceleration.…”
Section: Introductionmentioning
confidence: 99%